Perancangan Ulang Mal Pelayanan Publik Lampung Tengah Dengan Pendekatan Perilaku - Abiyyu Kanaz, Nabilly; Akhmadi; Firmansyah, Rangga (Telkom University, 2024)
This research proposes an interior design aimed at enhancing efficiency and transparency in public service malls, which often face challenges such as complex service processes and a lack of transparency. Using literature review and case analysis, the study identifies deficiencies in current design and operations. The result is an interior design that optimizes user flow, space, the use of information technology, and visual elements to strengthen transparency and clarity of information. This redesign has been shown to improve service efficiency and access to information, as well as increase public trust in public service institutions. The study provides guidelines for stakeholders in designing efficient, transparent, and user-friendly public service malls. Keywords: public service mall, public services, efficiency